ANALISA KEKERASAN PISAU POTONG (PARANG) PADA PROSES PENEMPAAN (FORGING) - Akhmad Syarief (Universitas Lambung Mangkurat, 2008)
Forging is workmanship of steel or metal become form which good for by using compressor or hammer. Intention of this research to analyse the quality of from steel result of process forge in the bearing of with storey;level hardness of him. Besides to know the quality of cooler media able to be used so that can improve;repair the nature of physical and nature of is mechanical the than steel result of forging. From examination of hardness which can know that at process treatment of heat with different cooler media (air, water, and salt water), highest hardness is cooler media irrigate salt. But for the making of crosscut knife (parang) is water. Because the hardness storey;level of high enough and the him of compared to lower of salt.